The independent and joint relationships between dietary antioxidant intake with risk of chronic obstructive pulmonary disease and all-cause mortality: insights from NHANES - Xu, Yifeng; Yan, Zhaoqi; Li, Keke; Liu, Liangji; Xu, Lei (Frontiers in Public Health, 2025)
BackgroundNumerous studies have indicated that a diet rich in antioxidants can prevent Chronic Obstructive Pulmonary Disease (COPD). However, the relationship between combined dietary antioxidant intake and the risk of COPD remains unclear. The Comprehensive Dietary Antioxidant Index (CDAI) is a composite score of various dietary antioxidants, including vitamins A, C, E, zinc, selenium, and carotenoids. In this study, we examined the independent and joint associations of CDAI with the risk of COPD and all-cause mortality.MethodsThe analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2013 to 2018. Multivariable weighted logistic and Cox regression models were employed to evaluate the correlations of CDAI (including vitamins A, C, E, zinc, selenium, and carotenoids) with the risk of COPD and all-cause mortality. Restricted cubic spline models were used to examine potential non-linear relationships. Sensitivity and stratified analyses were conducted to assess the robustness of the results.ResultsIn this study, compared to the lowest quartile, the highest quartile of CDAI levels was significantly negatively associated with the risk of COPD (Odds Ratio [OR]: 0.47; 95% Confidence Interval [CI]: 0.22–0.97), exhibiting a non-linear relationship. Additionally, vitamins A, C, E, zinc, selenium, and carotenoids were also negatively associated with the risk of COPD. Furthermore, dietary antioxidant zinc in the second quartile (Hazard Ratio [HR]: 0.25; 95% CI: 0.10–0.62) was negatively associated with the risk of all-cause mortality compared to the lowest quartile. Subgroup analysis results remained stable, and sensitivity analysis did not support the association between selenium and the risk of COPD, with no substantial changes in the remaining associations.ConclusionHigher CDAI is inversely associated with the risk of COPD, and appropriate intake of the dietary antioxidant zinc may reduce all-cause mortality in COPD patients.